Two new distribution records of Dendrobium (Orchidaceae), with an updated checklist of Dendrobium for Laos - Phonepaseuth, Phongphayboun; Souvannakhoummane, Keooudone; Xayyasith, Santi; Keovongsy, Chanthavong; Soulida, Khamnuk; Souladeth, Phetlasy (Thai Forest Bulletin (Botany), 2023)
Two new records of Dendrobium, D. daklakense, and D. metrium, are reported for the flora of Laos for the first time. Photographs, information on habitat and ecology, vernacular names and additional notes for each species are given based on collections from Dak Cheung Plateau, Sekong Province (D. daklakense), and Phou Khao Khouay National Park, Vientiane Province (D. metrium). An updated checklist with classification section of Dendrobium in Laos is also provided.